Complexes of SiH22+ with carbodiphosphorane and analogues {R(PPh3)2} in unusual bonding mode (E = C, Si, Ge, Sn, Pb) - Ai Nhung, Nguyen Thi; Ly, Nguyen Van; Duong, Tran; Tat, Pham Van (Vietnam Journal of Chemistry, 2014)
Quantum chemical calculations at the BP86 level with various basis sets (SVP, TZVPP) were carried out for complexes of carbodiphosphorane analogues E(PPh3)2 with E = C, Si, Ge, Sn, Pb. The equilibrium geometries of the complexes [SiH22+–{E(PPh3)2}] (Si2+-1E) possess the carbodiphosphorane ligand 1C is slightly bonded in a tilted way to SiH22+ in the complex Si2+-1C, whereas the heavier group-14 ligands E(PPh3)2 (E = Si, Ge, Sn, Pb) in the complexes Si2+-1Si – Si2+-1Pb are strongly bonded in side-on fashions. The surprising structures SiH22+-tetrylone complexes possess a strong Si-C1 bond between the Si atom of the SiH22+ fragment and atom C1 of the phenyl group. The trend of the bond dissociation energies  (BDEs) for the Si-E bond in the Si2+-1E complexes is Si2+-1C ~ Si2+-1Si ~ Si2+-1Ge < Si2+-1Sn < Si2+-1Pb. Bonding analysis of the complexes shows that the Si-E bonds have a significant contribution from H2Si2+←E(PPh3)2 π-donation. Keywords: Donor-acceptor interactions; bonding analysis; density functional theory, bond dissociation energy